Dependent capitalism and its distinctive forms of government in the light of the Marxist Dependency Theory - Leomar Rippel (Ибероамериканские тетради, 2023)
The purpose of this work is to analyze the particular forms of government that arise under conditions of dependent capitalism. The author analyzes the features of the uneven development of dependent countries and suggests that in such countries a special form of development of capitalism has formed. As a theoretical basis, the author uses the Marxist theory of dependence. As a result of the study, the author concludes that a form of government in dependent states brings about conditions in which national resources and capital flow to developed capitalist countries. As a result dependent countries lose part of their sovereignty, and an authoritarian political regime based on the working class becomes a necessary condition for maintaining dependence on the capitalist center.